Akkermansia muciniphila Protects Against Psychological Disorder-Induced Gut Microbiota-Mediated Colonic Mucosal Barrier Damage and Aggravation of Colitis - Chen, Tuo; Wang, Rong; Duan, Zhenglan; Yuan, Xiaomin; Ding, Yang; Feng, Zeyu; Bu, Fan; Liu, Li; Wang, Qiong; Zhou, Jinyong; Zhu, Lei; Ni, Qing; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Psychological disorders are associated with increased risk of severe inflammatory bowel disease (IBD) by causing gut microbiota dysbiosis and colonic mucosal barrier damage. However, the interaction between chronic restraint stress (CRS), gut microbiota composition, and colonic mucus remains unclear. We demonstrated that mice under CRS conditions exhibited alterations in microbiota composition, disruption of colonic mucus, and aggravation of colitis. In addition, the abundance of Akkermansia muciniphila was significantly decreased in mice under CRS and UC patients with depression, and positively associated with the expression of MUC2. After antibiotic treatment, the recipient mice colonized with CRS microbiota showed barrier defects and severe colitis. Administration of Akkermansia muciniphila was found to restore colonic mucus and modify the gut microbiota. We confirm that CRS-mediated gut microbiota dysbiosis results in colonic mucosal barrier damage and aggravation of colitis. Our results suggest that A. muciniphila is expected to be a potential probiotic to protect and treat colonic mucus that is involved in IBD with psychological disorders.